TOWARDS RESILIENT URBAN FUTURES: LAND USE CHANGE, FLOOD RISK, AND THE ROLE OF SUSTAINABLE DRAINAGE SYSTEMS IN KUANTAN TENGAH DISTRICT - Chitra Hermawan; Reni Suryanita; Aras Mulyadi; Yohannes Firzal (Universitas Trisakti, 2025)
Sustainable Urban Drainage Systems (SUDS) are considered an innovative approach to urban water management, but their application in Indonesia is still very limited. Aim: This study was aimed to analyze the impact of land use change on runoff coefficient and its implication for socio-economic resilience in post-flood conditions in Kuantan Tengah District, Riau Province. Methodology and results: The research applied a spatial-hydrological and socio-economic approach, integrating drone imagery, GIS-based land classification, runoff coefficient analysis, field drainage assessment, and community surveys. Results revealed that the average runoff coefficient (Cr) increased to 0.57 due to land conversion into impervious surfaces, especially residential and road areas. This condition led to inadequate drainage capacity and contributed to urban flooding. Socio-economic impacts identified include infrastructure damage, income loss in local businesses, health problems, and psychological stress. SWOT analysis highlighted institutional strengths and public awareness, but also emphasized weak ecosystem-based management. Conclusion, significance and impact study: A Sustainable Urban Drainage System (SUDS) model was proposed to overcome these challenges, combining green infrastructure, zoning policy, SOP (standard operating procedures) for drainage maintenance, and community participation. This study provides a novel integrative framework for urban flood risk mitigation based on hydrological and socio-economic indicators and offers policy insights for sustainable spatial planning in flood-prone regions. The solutions offered directly support several Sustainable Development Goals (SDGs), particularly SDG 11 on Sustainable Cities and Communities, SDG 6 on Clean Water and Sanitation, and SDG 13 on Climate Action.